ABCB1 polymorphisms and neuropsychiatric adverse events in oseltamivir-treated children during influenza H1N1/09 pandemia. (October 2011) - L''Huillier, Arnaud G; Ing Lorenzini, Kuntheavy; Crisinel, Pierre-Alex; Rebsamen, Michela C; Fluss, Joel; Korff, Christian M; Barbe, Remy P; Siegrist, Claire-Anne; Dayer, Pierre; Posfay-Barbe, Klara M; Desmeules, Jules A
Aims: To examine the safety profile of oseltamivir in children and evaluate the impact of P-glycoprotein polymorphisms on the incidence of neuropsychiatric adverse events (NPAE) in oseltamivir-treated children.Subjects & methods: This prospective cohort study was conducted in our tertiary care pediatric hospital (University Hospitals of Geneva, Switzerland) during the H1N1 pandemia, between 1 October 2009 and 31 January 2010. All newborn to 18 year-old patients presenting at the emergency department with a flu-like illness were eligible for inclusion. Adverse events were systematically recorded by pediatricians and/or by parents at home using a diary card, with a 30-day follow-up period. The causality assessment of oseltamivir in NPAE was performed by two clinical pharmacologists. After informed consent, enrolled patients were also genotyped for ABCB1 3435C>T (rs1045642) and 2677G>T/A (rs2032582) polymorphisms.Results: Among the 42 H1N1-infected, oseltamivir-treated children who were genotyped for ABCB1 3435C>T and 2677G>T/A variants, 36% presented NPAE. When examining the association between the diplotype and the development of NPAE, we observed that the frequency of NPAE displayed a 'genotype-trend effect'' with the variant and the wild-type subgroups at the two far ends. A total of 11% of the 2677GG–3435CC individuals (wild-type homozygous) presented NPAE, compared with 39% of the individuals being heterozygous for at least one variant allele and 67% of the 2677TT–3435TT individuals (homozygous variants) (p = 0.149, nonsignificant).Conclusion: These observations suggest a potential influence of ABCB1 polymorphisms in oseltamivir-related NPAE, maybe as a result of an enhanced permeability of the blood–brain barrier to oseltamivir. Original submitted 26 April 2011; revision submitted 30th June 2011